Histological and Histochemical Study of the Exocrine Pancreas in Madras Red Sheep (Ovis aries) - Prakash, Piyush; Kumary, S. Usha; Kannan, T. A.; Ramesh, Geetha; Basha, Sabiha Hayath (Indian Journal of Veterinary Anatomy, 2018)
Microanatomical studies on the pancreas of different post-natal age groups of Madras red sheep was carried out. Pancreas consisted of both exocrine and endocrine parts where former formed the major portion. In all the age groups, pancreas was covered by a thin capsule from which septa arose and divided the glands in lobes and lobules. Blood vessels and nerve fibres were seen in the interlobular connective tissue. The exocrine portionconsisted of secretory units (acini) and components of duct system. The duct system of the exocrine pancreas comprised of intercalated, intralobular, interlobular and pancreatic ducts. PAS and alcian blue positive reaction was noticed in the columnar epithelium on interlobular and pancreatic ducts. Lipid droplets were noticed beneath the capsule and in the interlobular septa in all the age groups. Distinct metachromasia was seen in the mast cells of the periductal connective tissue of interlobular and pancreatic ducts in all the age groups. The exocrine portion ofthe pancreas showed positive result for the activity of acid phosphatase, alkaline phosphatase, amylase, carbonic anhydrase, cholinesterase, cytochrome oxidase, lipase, glucose 6-phosphatase and succinic dehydrogenase. Most of the enzymes showed an increase in the activity as the age of animal advanced.